Potential Contribution Of Sharia Micro Financing On Poverty Reduction In Slum Communities In Makassar - Hurriah Ali Hasan; Saidin Mansyur (Universitas Muhammadiyah Makassar, 2019)
Poverty is a problem faced by many countries. A country that has a high number of poor people, will always face various cases as a result of poverty, namely low education, high unemployment, health problems, criminal cases and prone to security problems. That is because the poor people not only lack money, but also do not have access to health services, food and education, so they are vulnerable to illness, malnutrition, and unable to get a good education. Considering its impact on people's lives, it is deemed necessary to take actions that can reduce poverty. Governments in many countries and international institutions have also sought to help the poor throughout the world, through microfinance programs. This effort has succeeded in reducing poverty at the global level. On the other hand, poverty is still quite high. The dependence of the poor on poverty alleviation programs from the government often leads to community dependence on the government. They are just waiting for help to stay alive, so they cannot get out of the cycle of poverty. Therefore, in efforts to alleviate poverty, the important thing to do by the government and institutions involved in poverty reduction is to encourage the independence of the poor so that they can get out of the poverty circle by their own efforts. One effort to encourage the independence of the poor is to provide capital so that they can build their own business activities. In some circumstances, microfinance can be a strategy to provide a way out for the poor to escape poverty. This study aims to identify the potential contribution of Islamic microfinance to reduce poverty in slums in Makassar. The method used in this study is qualitative, in which data are collected through in-depth interviews with slum communities who have not been touched by access to financial institutions. Other interviews were conducted with the management of Islamic microfinance institutions. Interviews found that urban communities living in slums wanted to access financial institutions, but did not have the opportunity. While from the LKMS, it was stated that there are many financing programs provided for the poor. This shows that the opportunity to reduce poverty is very good with the large potential contribution of LKMS in encouraging the independence of the poor through business activities.Keywords: Sharia Microfinance Institutions, Poverty, Slum Communities